Consuming Atmospheres Designing, Experiencing, and Researching Atmospheres in Consumption Spaces - Steadman, Chloe; Coffin, Jack (Taylor & Francis, 2024)
consuming atmospheres, marketing, marketing research, consumer experience, consumer culture